2004
DOI: 10.1088/0957-4484/16/1/021
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-thin porous anodic alumina films with self-ordered cylindrical vertical pores on a p-type silicon substrate

Abstract: Ultra-thin alumina films with self-ordered cylindrical vertical pores were fabricated on a p-type silicon substrate by anodization of Al films with thickness in the range of 30–500 nm in sulfuric or oxalic acid aqueous solutions. In both cases the pores were arranged in hexagonal cells in a close-packed structure and their diameter and density depended on the electrochemical solution used. In the case of sulfuric acid both 30 and 500 nm Al films resulted in a similar uniform porous structure using exactly the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 16 publications
2
47
0
2
Order By: Relevance
“…In (a) and (c) the thickness of the Al film before anodization was 500 nm, while in (b) and (d) it was 30 nm. The circle around each pore that we observe in images from thinner samples reflects a void of larger diameter below the pore; identified in cross sectional TEM images [12] (see also figure 3a). We have to note here that by changing the anodization conditions, it is possible to find conditions for which the resulting films are identical for both thicker and thinner films.…”
Section: Fully Anodized Thin Porous Anodic Alumina Films On Si In Twomentioning
confidence: 77%
See 2 more Smart Citations
“…In (a) and (c) the thickness of the Al film before anodization was 500 nm, while in (b) and (d) it was 30 nm. The circle around each pore that we observe in images from thinner samples reflects a void of larger diameter below the pore; identified in cross sectional TEM images [12] (see also figure 3a). We have to note here that by changing the anodization conditions, it is possible to find conditions for which the resulting films are identical for both thicker and thinner films.…”
Section: Fully Anodized Thin Porous Anodic Alumina Films On Si In Twomentioning
confidence: 77%
“…Otherwise, phases II and III should coincide. If we stop anodization when the current density starts to fall to zero (end of phase III), the interface of alumina with Si shows the typical form illustrated in figure 3a, where we identify a void between a thin alumina barrier layer at the bottom of the pore and the silicon substrate [12][13]. The barrier layer is easily dissolved if the sample is immersed in a 5% in weight phosphoric acid aqueous solution for 2-3 minutes and then the pore is connected to the silicon substrate.…”
Section: Anodization Phasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The native silicon oxide of p-type Si was removed using 48% HF acid solution for 30 s prior to deposition of the Al film. The samples were annealed at 500°C for 3,6,15,18, and 24 h in a conventional furnace at a pressure of 3 ϫ 10 −4 Pa to relax the internal stress and to promote grain growth of the polycrystalline Al thin films.…”
mentioning
confidence: 99%
“…Kokonou et al 18 reported that for Al films with thicknesses of 500 nm anodized with electrolytes, oxalic, or sulfuric acid solutions, D p values around 30-40 nm were obtained. This is in good agreement with the expected values calculated from the proportionality constant, 1.29 nm V −1 .…”
mentioning
confidence: 99%